Detection and Quantification of Klebsiella pneumoniae in Fecal Samples Using Digital Droplet PCR in Comparison with Real-Time PCR - Junxia Feng; Xiaohu Cui; Bing Du; Hanqing Zhao; Yanling Feng; Jinghua Cui; Chao Yan; Lin Gan; Zheng Fan; Tongtong Fu; Ziying Xu; Zihui Yu; et al. (Microbiology Spectrum, 2023)
ABSTRACT This study aimed to develop a rapid and sensitive droplet digital PCR (ddPCR) assay for the specific detection of Klebsiella pneumoniae in fecal samples, and to evaluate its application in the clinic by comparison with real-time PCR assay and conventional microbial culture. Specific primers and a probe targeting the K. pneumoniae hemolysin (khe) gene were designed. Thirteen other pathogens were used to evaluate the specificity of the primers and probe. A recombinant plasmid containing the khe gene was constructed and used to assess the sensitivity, repeatability, and reproducibility of the ddPCR. Clinical fecal samples (n = 103) were collected and tested by the ddPCR, real-time PCR, and conventional microbial culture methods. The detection limit of ddPCR for K. pneumoniae was 1.1 copies/μL, about a 10-fold increase in sensitivity compared with real-time PCR. The ddPCR was negative for the 13 pathogens other than K. pneumoniae, confirming its high specificity. Clinical fecal samples gave a higher rate of positivity in the K. pneumoniae ddPCR assay than in analysis by real-time PCR or conventional culture. ddPCR also showed less inhibition by the inhibitor in fecal sample than real-time PCR. Thus, we established a sensitive and effective ddPCR-based assay method for K. pneumoniae. It could be a useful tool for K. pneumoniae detection in feces and may serve as a reliable method to identify causal pathogens and help guide treatment decisions. IMPORTANCE Klebsiella pneumoniae can cause a range of illnesses and has a high colonization rate in the human gut, making it crucial to develop an efficient method for detecting K. pneumoniae in fecal samples.